On the influence of free space in topology optimization of electro-active polymers - Dev, Chaitanya; Stankiewicz, Gabriel; Steinmann, Paul (Structural and Multidisciplinary Optimization, 2023)
This study investigates the impact of the surrounding free space on the topology optimization (TO) of electro-active polymers (EAPs). It is well understood that, under the application of an electric field, the deformation of an EAP is not solely determined by the field distribution within the body, but also by the distribution in the free space surrounding it. This is particularly true for electronic EAP, which are emerging as leading candidates for developing artificial muscles. Our study specifically focuses on understanding the influence of the free space in the context of density-based TO. We model the free space as an extended void region around the design domain. Our numerical experiments focus on EAP actuators and take into account their geometrical nonlinear behavior. The results show that incorporating the surrounding free space has a significant impact on the performance of the optimized EAPs with low electric permittivity. This makes it essential to consider in real-world applications.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Electro-active polymers; Free space; Topology optimization